Melt-rock interaction as a factor controlling evolution of chromite and olivine in dunite - case study from the Kukes Massif (Mirdita ophiolite, Albania) - Mikrut,J.; Matusiak-Malek,M.; Ceuleneer,G.; Gregoire,M.; Onuzi,K. (Journal of Geosciences, 2024)
The ultramafic Kukes Massif is located in the eastern part of the Mirdita ophiolite (N Albania), which is recognised as representing Supra-Subduction lithosphere. It comprises a thick (0.8-2.5 km) dunite zone containing abundant occurrences of chromite ores and is cut by orthopyroxenitic and clinopyroxenitic veins. In this paper we focus on the genesis and evolution of olivine and chromite forming dunite in the northern part of the Kukes Massif. The chemical composition of minerals in dunites is highly variabile and apparent at outcrop scale. The most significant changes are recorded by olivine, which contains over 90 Fo in the host dunite but decreases to 87.5 in proximity of clinopyroxenitic veins. The composition of spinel is also sensitive to the presence of veins: in host dunite its Cr# is over 80 (chromite type I), whereas the presence of veins causes its decrease to 68 (type II). Clinopyroxene in vein-forming clinopyroxenite has Mg# from 86 to 92 and is Al-rich (Al2O3 0.8-2.6 wt. %). Orthopyroxene forms orthopyroxenites (Mg# 90-93, Al2O3 0.2-1.6 wt. %), but also screens (Mg# 83-91, Al2O3 0.8-2.4 wt. %) at the contact between clinopyroxenite veins and the host dunite.The thick dunitic sequence at Kukes must have been formed as a result of intensive percolation of possibly boninitic melt through parental harzburgite. Another step in the evolution of the Kukes massif was related to intrusion of the pyroxenitic veins. These melts were not equilibrated with the host dunite and led to metasomatic modification of chromite and olivine, increasing Al2O3 content in former (from 6-8 up to 18 wt. %) and decreasing Fo (extremely from 92 to 87.5) in the latter. The process is evident proximal to clinopyroxenite veins, but a subtle effect is also recorded in the chemical composition of dunite contacting orthopyroxenite, leading to increase in Fe2O3 content. Metasomatism modified the composition of dunites in a zone of 0.5 m around pyroxenites. Our studies indicate a multistage evolution of the SSZ peridotites and show that its deciphering requires careful mineralogical examination.
Keywords: dunite; chromite; melt-rock interaction; Mirdita ophiolite; pyroxenitic veins